Validation of the rabbit pain behaviour scale (RPBS) to assess acute postoperative pain in rabbits (Oryctolagus cuniculus) - Pinho, Renata Haddad [UNESP]; Luna, Stelio Pacca Loureiro [UNESP]; Trindade, Pedro Henrique Esteves [UNESP]; Justo, André Augusto; Cima, Daniela Santilli [UNESP]; Fonseca, Mariana Werneck [UNESP]; Minto, Bruno Watanabe [UNESP]; Rocha, Fabiana Del Lama [UNESP]; Miller, Amy; Flecknell, Paul; Leach, Matthew C. (Public Library of Science (PLoS), 2022)
Considering the widespread use of rabbits in research that potentially causes pain and discomfort and the limited number of pain assessment validated tools in this species, we aimed to develop and validate a scale of acute postoperative pain in rabbits (RPBS). Footage of 58 rabbits from previous studies were used, recorded at ‘baseline’ (before orthopaedic and soft tissue surgeries), ‘pain’ (after surgery), ‘analgesia’ (after analgesic), and ‘24h post’ (24 hours after surgery). The videos were randomised and assessed twice by four evaluators, within one-month interval between evaluations. After content validation, RBPS was further refined using the criteria from the validation. According to the principal component analysis, RPBS was considered unidimensional. The intra- and inter-observer reliability was excellent (ICC>0.80) for all evaluators. There was a high Spearman’s correlation of the RPBS with unidimensional scales (>0.80) and a moderate correlation with the Rabbit Grimace Scale (0.68), confirming criterion validity. According to the mixed linear model, the scale was responsive, shown by the increase in pain scores after surgery. Construct validity was confirmed by known-group approach and internal relationships among items. Adequate item-total correlation (>0.3) was observed for all items, except for the attention to the affected area (0.04). The internal consistency was very good (Cronbach’s α coefficient = 0.78; Mcdonald’s ω coefficient = 0.83). The cut-off score for rescue analgesia was ≥3, with an area under the curve >0.95, demonstrating a high discriminatory capacity of the instrument. Scores 3 and 4 were within the uncertainty diagnostic zone. Specificity was 87% and sensitivity was 90%. It was concluded that the RPBS presented content, criterion, and construct validities, responsiveness, and reliability to assess acute pain in rabbits submitted to orthopaedic and soft tissue surgeries. The cut-off for rescue analgesia serves as a basis for the administration of analgesics to rabbits submitted to painful procedures.